PENGARUH PENAMBAHAN SUKROSA DAN ASAM ASETAT GLACIAL TERHADAP KUALITAS NATA DARI WHEY TAHU DAN SUBSTRAT AIR KELAPA - Fivien Wijayanti; Sri Kumalaningsih; Mas'ud Effendi (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2012)
The purpose of the implementation of this study is to find out the characteristics of nata de soya which is made from the whey of soybean cake and substrate irrigate coconut water  in terms of physical, chemical and organoleptic (consumer acceptance studies) and to know the effect of the addition of glacial acetic acid and sucrose on the quality of nata de soya. Experimental design used in this study is a randomized block design (RAK) made with 2 factors and consists of three levels, namely the concentration of Sucrose (S1) = 40 grams, (S2) = 45 grams, (S3) =50 grams and G1=10 ml, G2 = 7,5 ml, G3=5 ml. Research conducted includes, yield, texture, color, crude fiber, moisture Keywords: Nata de soya, acetate acid of glacial, Sucrose